Portable pepper collecter / Azman Zulkarnain, Muhammad Izhar Dahli and Mohd Norazim Ramnor - Zulkarnain, Azman; Dahli, Muhammad Izhar; Ramnor, Mohd Norazim (Faculty of Plantation and Agrotechnology, 2023)
Black pepper, (Piper nigrum), is a agricultural crop which contains many nutritional, economical, and medicinal benefits. According to the Food and Agriculture Organization Corporate and Statistical Database (FAOSTAT), in the year 2020, Malaysia is the 7th largest producer of pepper in the world. Early literature on pepper planting in Malaysia shows it was first planted in Langkawi in 1619. In spite of becoming one of the largest producer in the world, pepper cultivation in Malaysia is steadily declining as the industry is facing competitive mainly from oil palm industry as farmers are changing their crop from pepper to oil palm. In order to kept competitive with other producer nations, new inventions that can help increase the production of pepper.